Pengaruh Keadilan Organisasi terhadap Kinerja dengan Efektivitas Kerja sebagai Variabel Intervening pada Karyawan PT. Perkebunan Nusantara IV Regional IV Unit Usaha Rimbo Satu Kabupaten Tebo - Hesti Safira; Khairun A Roni; Delila Fitri Harahab (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study aims to analyze the influence of Organizational Justice on Performance with Work Effectiveness as an Intervening Variable among employees of PT Perkebunan Nusantara IV Regional IV Rimbo First Business Unit, Tebo Regency.A sample of 78 respondents was selected using the Total Sampling technique (saturation sampling). Based on the data processing results using SEM-PLS, it was found that, directly (direct effect), Organizational Justice significantly affects Employee Performance, Organizational Justice significantly affects Work Effectiveness, and Work Effectiveness significantly affects Employee Performance. Then, indirectly (Indirect Effect), Organizational Justice significantly affects Employee Performance mediated by Work Effectiveness.